Lao People's Democratic Republic Responding to Rice Price Inflation - World Bank (World Bank, Washington, DC, 2017)
The objective of this policy note is to identify likely factors driving rice prices and suggest options to manage rice price volatility in the future. It also provides a snapshot of recent developments in the rice sector, and describes rice and food price trends and their implications. Based on these findings, the note discusses policy options. The policy brief has six chapters, including this introduction. Chapter two provides a brief outline of the rice sector. Chapter three describes recent trends in world and Lao food prices. It also provides insights into likely macroeconomic and household welfare impacts of rice price inflation. Chapter four discusses the potential causes of rice price inflation, as suggested by other reports and people interviewed. Chapter five analyzes the role of the regional rice market in determining prices, which this policy brief identifies as the primary cause of the glutinous rice price hike. Chapter six concludes by presenting recommendations.